A Stakeholder Rationale for Risk Management - Gossy, Gregor (Springer, 2017)
Ordinarily, only the interests of shareholders, debtholders, and corporate management are taken into account when analyzing corporate financial decisions while the interests of non-financial stakeholders are often neglected.